A tradição do brinquedo de miriti no currículo das escolas do município de Abaetetuba: iniciando o debate - LOBATO, Lídia Sarges (Universidade Federal do Pará, 2020)
This article results from research that has as one of the objectives to analyze the gender relations in two production workshops of miriti toys. the ethnographic experience is ongoing and the production of information allows us to have introductory re ections because the daily observation and discussions with the interlocutors enabled our entry into the world of custom and culture of the place. the e work is organized as follows: we started with the invention of miriti toy tradition so then deal the handmade production and gendered common to the two workshops process. We ended with a reflection about the cultural pedagogy of workshops and the need for inclusion of the miriti toy tradition in the official curriculum of public schools.